2017
DOI: 10.1037/cep0000119
|View full text |Cite
|
Sign up to set email alerts
|

How different cultures look at faces depends on the interpersonal context.

Abstract: Culture can influence how we see and experience the world, and recent research shows that it even determines how we look at each other. Yet, most of these laboratory studies use images of faces that are deprived of any social context. In the real world, we not only look at people's faces to perceive who they are, but also to signal information back to them. It is unknown, therefore, within which interpersonal contexts cultural differences in looking at faces emerge. In the current study, we manipulated one asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Visual orienting to faces, for instance, has been shown to decrease significantly when participants sat in the same room with another person, compared to when participants saw a videotape of the same individual 18 , highlighting the importance of social presence in naturalistic settings. Furthermore, cultural differences have been found when faces on screen appeared to make direct eye contact with the participant, with East Asians scanning the nose and Western Caucasians fixating the eyes 19 . No cultural differences were observed, however, when the faces appeared to avert their gaze, thereby pointing to possible cultural differences in eye contact avoidance 19 , which has been proposed to act as a sign of respect in East Asian cultures 20,21 .…”
Section: Limitations Of Screen-based Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual orienting to faces, for instance, has been shown to decrease significantly when participants sat in the same room with another person, compared to when participants saw a videotape of the same individual 18 , highlighting the importance of social presence in naturalistic settings. Furthermore, cultural differences have been found when faces on screen appeared to make direct eye contact with the participant, with East Asians scanning the nose and Western Caucasians fixating the eyes 19 . No cultural differences were observed, however, when the faces appeared to avert their gaze, thereby pointing to possible cultural differences in eye contact avoidance 19 , which has been proposed to act as a sign of respect in East Asian cultures 20,21 .…”
Section: Limitations Of Screen-based Paradigmsmentioning
confidence: 99%
“…Furthermore, cultural differences have been found when faces on screen appeared to make direct eye contact with the participant, with East Asians scanning the nose and Western Caucasians fixating the eyes 19 . No cultural differences were observed, however, when the faces appeared to avert their gaze, thereby pointing to possible cultural differences in eye contact avoidance 19 , which has been proposed to act as a sign of respect in East Asian cultures 20,21 . To examine cultural modulations on naturalistic face scanning, studies will therefore need to take into account such sociocultural norms.…”
Section: Limitations Of Screen-based Paradigmsmentioning
confidence: 99%
“…For example, research has repeatedly shown that visual attention measured in the laboratory can differ from visual attention as it is employed in the real world (Kuhn, Teszka, Tenaw, & Kingstone, 2016;Risko, Laidlaw, Freeth, Foulsham, & Kingstone, 2012;Risko et al, 2016). When people look at others' faces, gaze patterns vary significantly depending on when looking at a live or pre-recorded video (Laidlaw, Foulsham, Kuhn, & Kingstone, 2011), or whether the face is looking directly at them or not (Gobel, Chen, & Richardson, 2017). Indeed, people are very much aware of social scripts that govern when it is appropriate to look and when it is not (Foulsham, Walker, & Kingstone, 2011;Laidlaw, Rothwell, & Kingstone, 2016;Wu, Bischof, & Kingstone, 2013).…”
Section: The Fourth Wall Of Cognitive Sciencementioning
confidence: 99%
“…For instance, direct gaze signals a desire to communicate ( Ho, Foulsham, & Kingstone, 2015 ; Kendon, 1967 ), it monitors facial displays of the other person to ensure mutual understanding ( Kleinke, 1986 ), it expresses affiliation or (dis)agreement ( Kendrick & Holler, 2017 ), attractiveness ( Georgescu et al, 2013 ), and threat or dominance ( Emery, 2000 ; Gobel et al, 2015 ). Conversely, averted gaze has been linked to preference for no interaction ( Foulsham, Walker, & Kingstone, 2011 ), conformity with social or cultural norms ( Gobel, Chen, & Richardson, 2017 ; Gobel et al, 2015 ; Laidlaw et al, 2011 ; also known as ‘civil inattention’, Goffman, 1963 ), and fear or submissive behaviour ( Emery, 2000 ; Gobel et al, 2015 ). The variety of social meanings that our eyes can convey makes our gaze a powerful tool for social interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that, if participants believed the person in the video would later see the recordings, they made more eye contact with the low rank model, and less with the high rank model. In these studies, the authors suggest that averted gaze in live (versus pre-recorded) settings signals the activation of previously acquired social norms, by which it is not polite to stare at someone ( Gobel et al, 2017 ). The effect of these social norms translates into active gaze disengagement because participants do not want to appear as either someone impolite or as an interaction partner to the stranger ( Foulsham et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%